2022
DOI: 10.3390/molecules27020439
|View full text |Cite
|
Sign up to set email alerts
|

Study on Synergistic Antioxidant Effect of Typical Functional Components of Hydroethanolic Leaf Extract from Ginkgo Biloba In Vitro

Abstract: The predicted anti-oxidation is related to apoptosis, proliferation, lipid metabolism, cell differentiation, and immune response. There are some differences in the antioxidant capacity of the four typical components of ginkgo biloba extract (EGb) including ginkgo flavone (GF), ginkgolide (G), procyanidins (OPC), and organic acids (OA), and any two members of them can exhibit apparent synergistic effects. The order of DPPH scavenging ability was: OPC > GF > OA > G. The scavenging ability of procyanidin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0
2

Year Published

2022
2022
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 23 publications
1
14
0
2
Order By: Relevance
“…Such compounds, such as vitamins C and E [ 31 , 32 , 33 ], and amino acids or proteins [ 33 , 34 , 35 ], typically found in peach and its products, were proportionally extracted in the UAE and MAE extracts. Alternatively, synergistic effects occurring between antiradical antioxidants in both extracts may have leveled the results of scavenging activities [ 36 , 37 ]. Nonetheless, it is reported that the antiradical potential of natural products does not necessarily match the reduction of Fe(III) to Fe(II) as measured by FRAP [ 38 ].…”
Section: Resultsmentioning
confidence: 99%
“…Such compounds, such as vitamins C and E [ 31 , 32 , 33 ], and amino acids or proteins [ 33 , 34 , 35 ], typically found in peach and its products, were proportionally extracted in the UAE and MAE extracts. Alternatively, synergistic effects occurring between antiradical antioxidants in both extracts may have leveled the results of scavenging activities [ 36 , 37 ]. Nonetheless, it is reported that the antiradical potential of natural products does not necessarily match the reduction of Fe(III) to Fe(II) as measured by FRAP [ 38 ].…”
Section: Resultsmentioning
confidence: 99%
“…The flavonoids in ginkgo are being researched by many scientists. However, most studies focus on monomeric flavonoids and biflavonoids are often neglected [ 13 , 14 , 15 ], e.g., in the review article by Liu et al [ 16 ], which focuses on the advances in chemical analysis and quality control of flavonoids in ginkgo, the presence of biflavonoids is hardly mentioned. To fill this gap in our knowledge of ginkgo flavonoids, the aim of the present study was to establish a tissue-specific profile of biflavonoids in ginkgo.…”
Section: Introductionmentioning
confidence: 99%
“…In mixtures of O-glucosylated flavonoids with Trolox or ascorbic acid, a negative non-additive effect (antagonism) was seen for quercetin and morin, while a synergistic interaction was found for rutin and naringin [48]. Synergistic and antagonistic interactions between components of Gingko biloba leaf extracts have been reported using the ABTS • reduction assay [49]. Thus, it cannot always be expected that ABTS • reduction by a summed compound will be equal to the sum of ABTS • reductions by individual compounds, and ABTS • reduction by a complex extract does not necessarily reflect the sum of the ABTS • -reducing abilities of its components.…”
Section: Interaction Between Antioxidantsmentioning
confidence: 98%
“…Interactions between low-molecular antioxidants leading to subadditive behavior in antioxidant activity assays have been reported [47][48][49]. In this study, we checked the interactions between Trolox, ascorbate and hispidulin as model compounds by comparing ABTS • reduction by single antioxidants and their combination (slopes of the lines of concentration dependence of absorbance decrease or AUC).…”
Section: Interaction Between Antioxidantsmentioning
confidence: 99%